DERMATOFIBROSARCOMA PROTUBERANS OF TRUNK IN A MALE PATIENT - Hashmi, Junaid Zia; Ghafoor, Ammarah; Hiraj, Masood ur Rauf Khan; Chaudhary, Waseem Abbas (Journal of Ayub Medical College Abbottabad, 2022)
Dermatofibrosarcoma protuberans is a rare cutaneous malignancy. Usual sites of origin are trunk and extremities. Aetiology of the condition is not well understood but a genetic basis is explained as a reciprocal translocation t (17l;22) (q22; q13). Distant metastasis is quite rare as it is mostly a locally advancing tumour. Histopathology is the most accurate investigation to make a diagnosis. Imaging is still required to rule out distant metastasis. Surgical excision is the treatment option for stage I tumours. Imatinib, a tyrosine kinase inhibitor, has shown promising results in management of locally advanced and metastatic disease.